THE ATTITUDES AND HABITS OF PATIENTS TOWARD USE OF HERBAL DRUGS - Stanojević, Milica; Nikolić, Jagoda; Jovanović, Marija; Kočović, Aleksandar; Milosavljević, Miloš N; Milosavljević, Milica N (Medicinski časopis, 2019)
Aim: The aim of study was to examine the factors associated with the use of herbal drugs among patients in Serbia, as well as to assess the attitudes and habits of patients toward the use of herbal drugs. Patients and methods: The study was designed as observational, cross-sectional study. The research was conducted during February 2018 in six community pharmacies across municipalities of Despotovac and Ćuprija. Study population consisted of adult volunteers of both genders and over 18 years of age who had purchased drugs in one of the six pharmacies involved in the study. Participants filled out the semi-structured questionnaires which had been specifically designed for purposes of this research. The questionnaire consisted of two parts. The first part comprised five questions relating to socio-demographic characteristics of participants, while the second part of the questionnaire was composed of eight questions concerning the use of herbal products. The study data were analyzed by descriptive and analytical statistics by SPSS statistical program. Results: There were 190 participants in total. The average age of the study subjects was 47.83 ± 15.9 years (the youngest was 18, while the oldest was 87 years old). Some form of herbal product used 145 (76.3%) participants. The most common reasons for the use of herbal drugs were common cold (22.6%), improving the digestion (8.9%), stimulation of immune system (7.5%), dermatological problems (7.5%), cough (4.8 %) and rheumatic complaints (4.8%). The most frequently, participants gained information on use of herbal drugs by pharmacists (26.9%), from sources provided by Internet (21.0%), by their physicians (11.8%) and by family members and friends (10.8%). Of the total number 67.7% of participants considered herbal drugs to be completely safe for use. Slightly more than half of the study subjects (52.7%) gave information on using the herbal drug to their physicians. The binary logistic regression analyses showed that herbal drugs were more commonly used by younger women, with a higher school or faculty degree who prefer to use herbal medicines compared to the other drugs. Conclusion: The results of our study have shown that herbal drugs had been more commonly used by younger women, with a higher school degree or faculty degree, and who have declared that prefer to use herbal drugs in relation to other drugs. Key words: complementary and alternative medicine, herbal drugs, community pharmacies.
Keywords: Questionnaires; Pharmacies; Herbals; Habits